ANALISIS SISTEM AKUNTANSI ANGGARAN BELANJA DANA INFRASTRUKTUR DI DESA TULUNG AGUNG PELALAWAN - Widiyanti, Widiyanti (LPPM STMIK Dharmapala Riau, 2021)
Based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 113 of 2014 concerning Village Financial Management,